ANALISIS MINAT BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA BERBANTUAN SOFTWARE GEOGEBRA DI KELAS V MADRASAH DARUL ULUM MANCILAN: Analisis Minat Belajar, Pembelajaran Matematika, Software Geogebra - Akmaliah, Vika Zida; Budi Setyo Lestari, Andika; Bahasa Indonesia, Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2024)
The aim of this research is to determine the effect of knowing the use of geogebra software on students' learning interest in square and rectangular flat building materials. The subjects of this research were 28 students in class V of Madrasah Darul Ulum Mancilan 12 women and 16 men. This study used quantitative descriptive and the instrument used, namely non-test containing questionnaires in the form of student statements on the interest in learning flat building material assisted by geogebra software with 20 statements consisting of 4 indicator. The results of this study showed an indicator of feeling happy the average percentage obtained 81.1% of the category was very high, both indicators of student interest Resulting in an average percentage of 82.8% in the very high category, the three indicators of student engagement with an average percentage of 72.5% in the high category and finally the engagement indicator produced an average percentage of 78.7% in the high category. The overall percentage of the analysis of student learning interest indicators resulted in 78.6% being in the high category.